Buy or bye? Investigating impulse buying behavior on e-commerce platforms - Briones, Darren Angelo (Animo Repository, 2021)
This research contributes to understanding the impulse buying behavior of consumers in e-commerce platforms and determining the factors that influence impulsive purchases. Using a mixed-method approach, e-impulse behavior was explored through the Stimulus-Organism-Response (S-O-R) and Impulse Buying Episode Frameworks. Survey data on purchasing on e-commerce and impulse buying from Generations Y and Z were analyzed via mediation analysis. Meanwhile, insights from interview questionnaire responses regarding e-impulse buying behavior were derived via data structure format. Mediation results indicate that impulse buying can either be triggered or inhibited by utilitarian or hedonic browsing with environmental stimuli partially mediating the effects. Based on interview responses, two distinct aggregate outcomes of impulse buying emerged: emotion-based and value-based. Parallel conclusions include how (1) impulse buying is experienced through the acceleration of the entire buying episode from the urge to buy all the way to post-purchase and how (2) e- commerce stimuli induce shoppers to satisfy emotional considerations or to quickly resolve intended purchase decisions. Thus, this can help to improve e-commerce platforms by developing profitable marketing schemes and also enhancing customer experience. This study can also be used to create awareness for consumers regarding impulse buying tendencies and the possible implications of using impulse buying triggers to influence consumer behavior.